Effect of molybdenum addition on hardenability of chromium-boron steels used for press hardening applications - Deepa M.; Sahoo G.; Dhua S.K. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Two laboratory heats of low-Carbon low-alloy steels, one with boron and chromium additions and other with boron, chromium and molybdenum additions were made and cast into pencil ingots. These ingots were hot-rolled to 2 mm sheets suitable for press hardening application in an experimental rolling mill. A detailed study was made on the effect of various alloying elements on the microstructure and mechanical properties of these steels. A significantly higher hardness (~496 VHN), yield strength (~1137 MPa) and ultimate tensile strength (~1673 MPa) with comparable elongation (~6%) could be achieved in the as rolled and water-quenched Mo-Cr-B steel in comparison to Cr-B steel under similar processing condition. Moreover, a reduction of critical cooling rate by10ºC/s was observed in this steel to obtain fully martensitic structure. The combined addition of boron, chromium and molybdenum was found to be more effective than that of boron and chromium in enhancing the microstructure and mechanical properties of boron-added steels. Additionally, a few hot compression tests were carried out to simulate the press hardening process of these experimental steels. It was found that one of the press hardening process parameters, viz., prior strain had a greater impact on the transformation behaviour of Cr-B and Mo-Cr-B steels during cooling.